Chile : Recent Economic Developments. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1996)
This paper examines the sources of growth in Chile and compares Chile's experience with that of other countries. Two alternative measures of the sources of growth for Chile are presented to facilitate comparisons with other studies. The first measure adjusts factor inputs for the degree of utilization (using the unemployment rate), and the second measure introduces an index of the quality of factor inputs. The paper presents estimates of potential output of Chile for 1971-95, and also discusses the projections of potential output growth for Chile over the medium term.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet